Simultaneous placement of FACTS devices using cuckoo search algorithm - Basanagouda N. Patil; S. B. Karajgi (Institute of Advanced Engineering and Science, 2020)
The power system deregulation requires thechange in reactive power compensation in the power system. The optimal placement of FACTs (Flexi ble AC transmission system) devices is mandatory to recalculate the reactive power compensation in deregulation case. The FACTs devices generally used in series and shunt conections. Here the various facts devices connected in series & shunt combination simultaneously. The optimal placement and sizing of the devices are done in this paper by formulating the objective function with minimization of cost of the generation and minimizing the cost of Facts devices. MALAB is used for writing the code. IEEE 14 bus system is used to here for testing the system. Placing the FACTs separately and simultaneously are studied in case study. Cuckoo search algorithm is used to identify the solution to the optimization problem.